2018
DOI: 10.1002/gj.3358
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon UPb ages from the Middle to Late Permian strata of the Yiyang area, southern North China Craton: Implications for the Mianlue oceanic crust subduction

Abstract: Basin formation and sedimentary development in the southern North China Craton (NCC) are closely related to the tectonic evolution of the Qinling Orogenic Belt (QOB). With the aim of revealing the coupling evolution between the QOB and southern NCC during the Late Palaeozoic, an investigation based on provenance analysis was performed in this study. We present new detrital zircon U–Pb data from the Middle–Late Permian sediments in the Yiyang area, southern NCC. The results show that detrital zircons, from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The detrital zircons in this study showed similar age characteristics to Late Permian in the Yiyang area [77], suggesting that the southern margin of the NCC and the NQOB was still characterized by shortening and elevation during the Early Triassic period. Additionally, the provenance of Jiyuan basin, which is located in north of the Yiyang area, transformed from the IMPU during the Late Permian to the NQOB during the Early Triassic [17,71].…”
Section: Constraints On the Paleogeographic And Tectonic Evolutionsupporting
confidence: 57%
See 2 more Smart Citations
“…The detrital zircons in this study showed similar age characteristics to Late Permian in the Yiyang area [77], suggesting that the southern margin of the NCC and the NQOB was still characterized by shortening and elevation during the Early Triassic period. Additionally, the provenance of Jiyuan basin, which is located in north of the Yiyang area, transformed from the IMPU during the Late Permian to the NQOB during the Early Triassic [17,71].…”
Section: Constraints On the Paleogeographic And Tectonic Evolutionsupporting
confidence: 57%
“…Therefore, based on the above evidence, we suggest that the provenances of the Liujiagou Formation in the Yiyang area were predominantly derived from both the southern margin of the NCC and from the NQOB. [68]; (e) Liujiagou Formation in the Xishan area, Taiyuan [69]; (f) Early Triassic strata in the Yan'an area, Ordos basin [70]; (g) third section of the Shiqianfeng Formation in the Qinshui basin [8]; (h) Liujiagou and Heshanggou formations in the Jiyuan basin [71]; (i) this study; (j) southern margin of the North China Craton [9,[72][73][74][75][76][77]; (k) North Qinling Orogenic Belt [53,56,78,79]. The diagrams are arranged geographically from north to south.…”
Section: Provenances Of the Liujiagou Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations, concerning detrital zircon chronology, have been successfully performed in the surrounding basins of the Qinling Orogen [4,[16][17][18][19][20][21][22][23][24][25]. The Qinling Orogen emerged as the closure of the Mianlve Ocean, which resulted in the final amalgamation of the South China Block and the North China Block [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These zircons can be a good object to collect some important information about the development of the Mianlve Ocean. In addition, provenance analysis of the Late Paleozoic sediments on the southern North China Block reveals that the tectonic uplift of the Qinling Orogen retreated during the Permian [20,[30][31][32][33]. However, there is a lack of data describing the Permian tectonic transition of the Qinling Orogen.…”
Section: Introductionmentioning
confidence: 99%